Pyridoxamine reduces inflammatory and microcirculatory abnormalities in metabolic dysfunction-associated steatohepatitis and modulates key factors in the hepatic AGE/ALE signaling pathway - Silvares, Raquel Rangel; Araujo, Beatriz Peres de; Pereira, Evelyn Nunes Goulart Da Silva; Rodrigues, Karine Lino; Barbosa, Juliana Magalhães Chaves; Silva, Juliana Florencio da; Silva, Vivian Vieira Dias da; Van de aarenburg, Marjo; Scheijen, Jean; Wouters, Kristiaan; Schalkwijk, Casper; Daliry, Anissa (Frontiers in Physiology, 2026)
Metabolic dysfunction-associated steatohepatitis (MASH) is an increasing public health concern for which new therapies are urgently needed. As growing evidence suggests that the advanced glycation/lipoxidation end products (AGE/ALE) pathway contribute to disease progression, we investigated how pyridoxamine modulates hepatic AGE/ALE-related signaling in a murine model of MASH, as well as its pharmacological impact on key features of MASH. C57BL/6 mice were fed either a standard diet (Control) or a high-fat, high-carbohydrate diet with 2% cholesterol (HFHC + CHOL2%) for 12 weeks. From weeks 6–12, subgroups of both diet groups received pyridoxamine (200 mg/kg/day), while the remaining mice received vehicles. Body and liver weights, blood glucose levels, adipose tissue distribution, liver histology, serum biochemistry, microcirculation, inflammatory cytokines, oxidative stress, and AGE/ALE signaling were assessed. The HFHC + CHOL2% group showed marked steatosis, inflammation, and impaired hepatic microcirculation. Pyridoxamine treatment attenuated metabolic and hepatic changes, reducing weight gain, hyperglycemia, fat accumulation, steatosis, collagen deposition, and the expression of proinflammatory cytokines associated with MASH. Pyridoxamine significantly reduced systemic levels of reactive dicarbonyls, such as glyoxal and 3-deoxyglucosone, and prevented the accumulation of fluorescent AGE/ALE and CML in both serum and liver. In addition, in the liver, pyridoxamine downregulates RAGE, CD36, and galectin-3 receptors, while upregulating detoxifying mediators, including AGE-R1 and glyoxalase-1. In this context, the metabolic and hepatoprotective effects of pyridoxamine appear to be associated with a rebalancing of key components of the AGE/ALE signalling pathway, potentially attenuating the toxic feedback loop that contributes.